A kind of fluorocarbon powder coating and preparation method thereof

By mixing polyvinylidene fluoride with a modified hydrogenated rosin alcohol with a modified curing agent and adding nano-hard particles, a fluorocarbon powder coating with strong adhesion and friction properties was prepared, which solved the problems of high curing temperature, long curing time and poor adhesion of existing fluorocarbon coatings, and achieved improved performance and reduced cost.

CN118956210BActive Publication Date: 2025-03-14JINHUA FRIENDSHIP PLASTIC POWDER TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411070707.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2025-03-14
Estimated Expiration
2044-08-06

AI Technical Summary

Technical Problem

Existing fluorocarbon coatings have problems such as high curing temperature, long curing time, poor adhesion and expensive prices, which limit their application.

Method used

By mixing polyvinylidene fluoride with a modified hydrogenated rosin alcohol with a modified curing agent, combining nano-hard particles, a fluorocarbon powder coating with strong adhesion and friction properties was prepared using specific process steps and reaction conditions.

Benefits of technology

The strong adhesion and friction properties of the coating are achieved, the curing temperature and time are reduced, the adhesion is improved, and the mechanical properties are enhanced through the use of nano-hard particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004980784850000061
    Figure BDA0004980784850000061
Patent Text Reader

Abstract

The invention discloses a fluorocarbon powder coating and a preparation method thereof, and relates to the technical field of powder coatings. The invention utilizes 3H-1,2-benzodisulfonol-3-ketone to modify hydrogenated rosin alcohol, thereby introducing the benzene ring in 3H-1,2-benzodisulfonol-3-ketone and the ternary aliphatic ring structure of hydrogenated rosin alcohol into a matrix, and then utilizes dihydroxyphenylalanine to modify m-xylene diisocyanate, and the presence of a large number of benzene rings hinders the overall sliding of the molecular chain after the matrix is ​​coated and cured, and the dihydroxyphenylalanine enables a strong adhesion relationship between the matrix and the substrate, thereby achieving strong adhesion and friction performance of the coating, and then, introducing a nano hard phase, the melted matrix can be wrapped around it to form an effective mechanical locking effect, forming a riveting behavior on the coating film, thereby further improving the friction resistance and mechanical properties of the matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder coatings, in particular to a fluorocarbon powder coating and a preparation method thereof. Background Art

[0002] Powder coating originated in the early 20th century. It is a new type of coating that is applied in the form of powder particles and forms a coating. It has the characteristics of being solvent-free, pollution-free, recyclable, environmentally friendly, energy-saving, and having high mechanical strength of the coating film. It conforms to the international principles of "economy, efficiency, ecology, and energy". Powder coating varieties are constantly being developed, coating technology is constantly being innovated, and the application fields are constantly expanding, from thick coatings to thin coatings that can be applied thinly; from mainly anti-corrosion functions to highly decorative and highly functional ones. Powder coating has become one of the most promising coating varieties, and is gradually replacing traditional soluble coatings. It is widely used in household appliances, metal components, building materials, automotive industry, telecommunications equipment, transportation equipment, pipeline industry and many other fields.

[0003] In recent years, fluoropolymers have been used in coatings to improve the hydrophobicity and oleophobicity of coatings and acid and alkali resistance due to their outstanding performance, and have received more and more attention; fluorine has special physical and chemical properties, such as the small fluorine atomic radius and the polarizability of the fluorocarbon bond, so the internal structure of fluoropolymer molecules is relatively dense, showing special surface properties such as low surface tension and hydrophobicity and oleophobicity. At the same time, the fluorocarbon bond energy is as high as 487.6kJ / mol, and the fluorine atoms tightly wrap the polymer carbon-carbon main chain in a spiral manner and fill the gaps, so that the integrity and density of the polymer molecular structure are protected to the maximum extent, and liquid and gas molecules can be prevented from entering the coating. Therefore, fluorocarbon coatings not only have good corrosion resistance, but also have excellent weather resistance and pollution resistance. They are usually used in steel structure buildings, bridges, ships, rail vehicles, pipelines, chemical facilities and color-coated steel plates for corrosion protection. Although fluorocarbon coatings have many excellent properties, their high curing temperature, long curing time, poor adhesion and high price limit their application. Summary of the invention

[0004] The object of the present invention is to provide a fluorocarbon powder coating and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a fluorocarbon powder coating, wherein the fluorocarbon powder coating is prepared by mixing modified hydrogenated rosin alcohol with a modified curing agent and polyvinylidene fluoride.

[0006] Furthermore, the modified hydrogenated rosin alcohol is prepared from hydrogenated rosin alcohol modified by 3H-1,2-benzodisulfonol-3-one.

[0007] Furthermore, the modified curing agent is prepared by modifying m-xylylene diisocyanate with dihydroxyphenylalanine.

[0008] Furthermore, a method for preparing a fluorocarbon powder coating comprises the following preparation steps:

[0009] (1) 3H-1,2-benzodisulfonol-3-one and hydrogenated rosin alcohol are mixed, 17 wt% sodium ethoxide aqueous solution is added dropwise under a nitrogen atmosphere, the mixture is stirred at 50-120 rpm for 30-60 min, and allowed to stand for 4-8 h to obtain modified hydrogenated rosin alcohol;

[0010] (2) dihydroxyphenylalanine, m-xylyl diisocyanate, and dibutyltin dilaurate are mixed in a mass ratio of 2:10 to 20:0.05, stirred at 40 to 80 rpm for 8 to 20 minutes under a nitrogen atmosphere, the pH of the solution is adjusted to 8.3 to 8.8 with a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution, and allowed to stand for 10 to 30 minutes to obtain a modified curing agent;

[0011] (3) The modified hydrogenated rosin alcohol, the modified curing agent, polyvinylidene fluoride and benzoin are mixed, stirred at 80-140 rpm for 2-10 min, the nano hard particles are added, stirred at 1500-2500 rpm for 2-6 min, then mixed at 120-150° C., extruded and cooled to room temperature, ground through a 160-220 mesh sieve to obtain a fluorocarbon powder coating.

[0012] Furthermore, the hydrogenated abietic alcohol in step (1) is composed of dehydroabietic alcohol, rosin methyl ester and dihydroabietic alcohol in a mass ratio of 1:07:2.

[0013] Furthermore, the dripping acceleration rate in step (1) is 0.1 to 0.8 mL / s.

[0014] Furthermore, in step (1), the mass ratio of 3H-1,2-benzodisulfonol-3-one, hydrogenated abietic alcohol, and 17 wt% sodium ethoxide aqueous solution is 1-5:9:0.5.

[0015] Furthermore, the nano-hard particles in step (3) are composed of nano-zirconium carbide, nano-chromium carbide and nano-boron carbide in a mass ratio of 1 to 3:0.5:0.1.

[0016] Furthermore, the molecular weight of the polyvinylidene fluoride in step (3) is 3×10 5 .

[0017] Furthermore, in step (3), the mass ratio of the modified hydrogenated rosin alcohol, the modified curing agent, polyvinylidene fluoride, benzoin, and the nano-hard particles is 5:25:50-100:0.5:1-2.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The present invention utilizes the ketone group in 3H-1,2-benzodisulfonol-3-one and the hydroxyl group in hydrogenated rosin alcohol to undergo a condensation reaction under the catalytic action of a base, thereby introducing the benzene ring in 3H-1,2-benzodisulfonol-3-one and the ternary aliphatic ring structure of hydrogenated rosin alcohol into a matrix, and then utilizes dihydroxyphenylalanine to graft onto the side chain of polyvinylidene fluoride through the isocyanate group in m-xylylene diisocyanate. The presence of a large number of benzene rings hinders the overall sliding of the molecular chain after the matrix is ​​coated and cured, and the catechol in the dihydroxyphenylalanine reacts with oxygen in the air to be converted into a quinone group, and then intramolecular cyclization occurs through an addition reaction, and isomers with different polymerization degrees are rearranged after double oxidation, and can branch with other reactants through its own multiple reaction sites. oxidized, and through other catechols and quinones with different degrees of oxidation, anti-disproportionation reactions occur to produce semiquinone free radicals, which are further coupled to form covalent bonds and form strong hydrogen bond coupling with polyvinylidene fluoride. At the same time, due to the interaction of multiple non-covalent forces, a strong adhesion relationship is generated between the matrix and the substrate, thereby achieving strong adhesion and friction properties of the coating. Then, a nano-hard phase is introduced into the polyvinylidene fluoride, and the melted matrix can be wrapped around it to form an effective mechanical locking effect, which can effectively protect the polymer molecular chains from slippage and shearing under the action of shear while destroying the continuity of the polymer matrix molecular chain. When the matrix is ​​rubbed, the nanoparticles will be embedded in the dual surface under mechanical action, forming a riveting behavior on the cured film, thereby enhancing the adhesion of the matrix to the substrate through physical adsorption. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe the method in detail. The test methods for various indicators of the fluorocarbon powder coatings prepared in the following examples are as follows:

[0022] The fluorocarbon powder coating is electrostatically sprayed on an iron plate and baked at 150°C for 10 minutes to form a cured film.

[0023] Adhesion: Take the same embodiment and comparative example and use ASTM D3363 as the reference standard to test the adhesion of the sample using the pull-off adhesion test;

[0024] Friction resistance: Take the same embodiment and comparative example and refer to GB / T15036.2, and use a paint film abrasion tester to detect the mass loss rate after rubbing 500 circles.

[0025] Mechanical properties: The same embodiment and comparative example were taken to test the impact strength according to GB / T1732; and the tensile strength of the sample was tested using a universal testing machine at a tensile rate of 10 mm / min.

[0026] Example 1

[0027] (1) Dehydroabietin alcohol, rosin methyl ester and dihydroabietin alcohol were mixed in a mass ratio of 1:07:2 to obtain hydrogenated abietin alcohol; 3H-1,2-benzodisulfonol-3-one and hydrogenated abietin alcohol were mixed, and a 17 wt % sodium ethoxide aqueous solution was added dropwise at 0.1 mL / s under a nitrogen atmosphere, stirred at 50 rpm for 30 min, and allowed to stand for 4 h to obtain modified hydrogenated abietin alcohol; the mass ratio of the 3H-1,2-benzodisulfonol-3-one, hydrogenated abietin alcohol and 17 wt % sodium ethoxide aqueous solution was 1:9:0.5;

[0028] (2) dihydroxyphenylalanine, m-xylyl diisocyanate, and dibutyltin dilaurate were mixed in a mass ratio of 2:10:0.05, stirred at 40 rpm for 8 min under a nitrogen atmosphere, the pH of the solution was adjusted to 8.3 with tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, and allowed to stand for 10 min to obtain a modified curing agent;

[0029] (3) Mixing nano zirconium carbide, nano chromium carbide, and nano boron carbide in a mass ratio of 1:0.5:0.1 to obtain nano hard particles; adding modified hydrogenated rosin alcohol, modified curing agent, and a molecular weight of 3×10 5 The polyvinylidene fluoride and benzoin were mixed, stirred at 80 rpm for 2 min, nano hard particles were added, stirred at 1500 rpm for 2 min, then mixed at 120 ° C, extruded and cooled to room temperature, ground through a 160 mesh sieve to obtain a fluorocarbon powder coating; the modified hydrogenated rosin alcohol, modified curing agent, molecular weight of 3×10 5 The mass ratio of polyvinylidene fluoride, benzoin and nano hard particles is 5:25:50:0.5:1.

[0030] Example 2

[0031] (1) Dehydroabietin alcohol, rosin methyl ester and dihydroabietin alcohol are mixed in a mass ratio of 1:07:2 to obtain hydrogenated abietin alcohol; 3H-1,2-benzodisulfonol-3-one and hydrogenated abietin alcohol are mixed, and a 17 wt % sodium ethoxide aqueous solution is added dropwise at 0.5 mL / s under a nitrogen atmosphere, stirred at 80 rpm for 50 min, and allowed to stand for 4 to 8 h to obtain modified hydrogenated abietin alcohol; the mass ratio of the 3H-1,2-benzodisulfonol-3-one, hydrogenated abietin alcohol and 17 wt % sodium ethoxide aqueous solution is 3:9:0.5;

[0032] (2) dihydroxyphenylalanine, m-xylyl diisocyanate, and dibutyltin dilaurate were mixed in a mass ratio of 2:15:0.05, stirred at 60 rpm for 15 min under a nitrogen atmosphere, and the pH of the solution was adjusted to 8.5 with tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, and allowed to stand for 15 min to obtain a modified curing agent;

[0033] (3) Mixing nano zirconium carbide, nano chromium carbide and nano boron carbide in a mass ratio of 2:0.5:0.1 to obtain nano hard particles; adding modified hydrogenated rosin alcohol, modified curing agent and a molecular weight of 3×10 5 The polyvinylidene fluoride and benzoin were mixed, stirred at 110 rpm for 5 min, nano hard particles were added, stirred at 2000 rpm for 4 min, then mixed at 130 ° C, extruded and cooled to room temperature, ground through a 190 mesh sieve to obtain a fluorocarbon powder coating; the modified hydrogenated rosin alcohol, modified curing agent, molecular weight of 3×10 5 The mass ratio of polyvinylidene fluoride, benzoin and nano hard particles is 5:25:75:0.5:1.5.

[0034] Example 3

[0035] (1) Dehydroabietin alcohol, methyl rosin, and dihydroabietin alcohol were mixed in a mass ratio of 1:07:2 to obtain hydrogenated abietin alcohol; 3H-1,2-benzodisulfonol-3-one and hydrogenated abietin alcohol were mixed, and a 17 wt % sodium ethoxide aqueous solution was added dropwise at 0.8 mL / s under a nitrogen atmosphere, stirred at 120 rpm for 60 min, and allowed to stand for 8 h to obtain modified hydrogenated abietin alcohol; the mass ratio of the 3H-1,2-benzodisulfonol-3-one, hydrogenated abietin alcohol, and 17 wt % sodium ethoxide aqueous solution was 5:9:0.5;

[0036] (2) dihydroxyphenylalanine, m-xylyl diisocyanate, and dibutyltin dilaurate were mixed in a mass ratio of 2:20:0.05, stirred at 80 rpm for 20 min under a nitrogen atmosphere, the pH of the solution was adjusted to 8.8 with tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, and allowed to stand for 30 min to obtain a modified curing agent;

[0037] (3) Mixing nano zirconium carbide, nano chromium carbide and nano boron carbide in a mass ratio of 3:0.5:0.1 to obtain nano hard particles; adding modified hydrogenated rosin alcohol, modified curing agent and a molecular weight of 3×10 5 The polyvinylidene fluoride and benzoin were mixed, stirred at 140 rpm for 10 min, nano hard particles were added, stirred at 2500 rpm for 6 min, then mixed at 150 ° C, extruded and cooled to room temperature, ground through a 220 mesh sieve to obtain a fluorocarbon powder coating; the modified hydrogenated rosin alcohol, modified curing agent, molecular weight 3×10 5 The mass ratio of polyvinylidene fluoride, benzoin and nano hard particles is 5:25:100:0.5:2.

[0038] Comparative Example 1

[0039] The difference between Comparative Example 1 and Example 2 is that step (1) is omitted; the remaining steps are the same as those of Example 2.

[0040] Comparative Example 2

[0041] The difference between Comparative Example 2 and Example 2 is that step (1) is omitted, and step (3) is changed to: mixing nano zirconium carbide, nano chromium carbide, and nano boron carbide in a mass ratio of 2:0.5:0.1 to obtain nano hard particles; adding a modified curing agent and a molecular weight of 3×10 5 The polyvinylidene fluoride and benzoin were mixed, stirred at 110 rpm for 5 min, nano hard particles were added, stirred at 2000 rpm for 4 min, then mixed at 130 ° C, extruded and cooled to room temperature, ground through a 190 mesh sieve to obtain a fluorocarbon powder coating; the modified curing agent, molecular weight of 3×10 5 The mass ratio of polyvinylidene fluoride, benzoin and nano hard particles is 25:75:0.5:1.5; the remaining steps are the same as those in Example 2.

[0042] Comparative Example 3

[0043] The difference between Comparative Example 3 and Example 2 is that there is no step (2), and the remaining steps are the same as Example 2.

[0044] Comparative Example 4

[0045] The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: modified hydrogenated rosin alcohol, modified curing agent, and a molecular weight of 3×10 5 The polyvinylidene fluoride and benzoin were mixed, stirred at 110 rpm for 5 min, nano hard particles were added, stirred at 2000 rpm for 4 min, then mixed at 130 ° C, extruded and cooled to room temperature, ground through a 190 mesh sieve to obtain a fluorocarbon powder coating; the modified hydrogenated rosin alcohol, modified curing agent, molecular weight of 3×10 5The mass ratio of polyvinylidene fluoride to benzoin is 5:25:75:0.5; the remaining steps are the same as those in Example 2.

[0046] Effect example

[0047] Table 1 below shows the performance analysis results of the fluorocarbon powder coatings of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0048] Table 1

[0049]

[0050] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention utilizes the ketone group in 3H-1,2-benzodisulfonol-3-one and the hydroxyl group in hydrogenated abietic alcohol to undergo a condensation reaction under the catalytic action of a base, thereby introducing the benzene ring in 3H-1,2-benzodisulfonol-3-one and the ternary aliphatic ring structure of hydrogenated abietic alcohol into the matrix, and then utilizes dihydroxyphenylalanine to be grafted onto the side chain of polyvinylidene fluoride through the isocyanate group in meta-xylylene diisocyanate. The presence of a large number of benzene rings hinders the overall sliding of the molecular chain after the matrix is ​​coated and cured, and the Peroxydihydroxyphenylalanine creates a strong adhesion relationship between the matrix and the substrate, achieving strong adhesion and friction performance of the coating. Then, a nano-hard phase is introduced into the polyvinylidene fluoride, and the melted matrix can wrap around it to form an effective mechanical locking effect, which can destroy the continuity of the polymer matrix molecular chain while effectively protecting the polymer molecular chain from slippage and shearing caused by shear. When the matrix is ​​rubbed, the nanoparticles will be embedded in the dual surface under mechanical action, forming a riveting behavior on the cured film, and enhancing the adhesion of the matrix to the substrate through physical adsorption.

[0051] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A fluorocarbon powder coating, characterized in that: The method comprises the following preparation steps: (1) Dehydroabietin alcohol, rosin methyl ester and dihydroabietin alcohol were mixed in a mass ratio of 1:7:2 to obtain hydrogenated abietin alcohol; 3H-1,2-benzodisulfonol-3-one and hydrogenated abietin alcohol were mixed, 17 wt% sodium ethoxide aqueous solution was added dropwise under nitrogen atmosphere, stirred at 50-120 rpm for 30-60 min, and allowed to stand for 4-8 h to obtain modified hydrogenated abietin alcohol; (2) Dihydroxyphenylalanine, m-xylene diisocyanate, and dibutyltin dilaurate are mixed in a mass ratio of 2:10-20:0.05, stirred at 40-80 rpm for 8-20 min under a nitrogen atmosphere, the pH of the solution is adjusted to 8.3-8.8 with tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, and allowed to stand for 10-30 min to obtain a modified curing agent; (3) The modified hydrogenated rosin alcohol, the modified curing agent, polyvinylidene fluoride and benzoin are mixed, stirred at 80-140 rpm for 2-10 min, the nano hard particles are added, stirred at 1500-2500 rpm for 2-6 min, then mixed at 120-150°C, extruded and cooled to room temperature, ground through a 160-220 mesh sieve to obtain a fluorocarbon powder coating.

2. A fluorocarbon powder coating according to claim 1, characterized in that: The dripping acceleration rate in step (1) is 0.1-0.8 mL / s.

3. A fluorocarbon powder coating according to claim 1, characterized in that: The mass ratio of the 3H-1,2-benzodisulfonol-3-one, hydrogenated abietic alcohol, and 17 wt % sodium ethoxide aqueous solution in step (1) is 1-5:9:0.

5.

4. A fluorocarbon powder coating according to claim 1, characterized in that: The nano-hard particles in step (3) are composed of nano-zirconium carbide, nano-chromium carbide and nano-boron carbide in a mass ratio of 1-3:0.5:0.

1.

5. A fluorocarbon powder coating according to claim 1, characterized in that: The molecular weight of the polyvinylidene fluoride in step (3) is 3×10 5 .

6. A fluorocarbon powder coating according to claim 1, characterized in that: In step (3), the mass ratio of the modified hydrogenated rosin alcohol, the modified curing agent, polyvinylidene fluoride, benzoin, and the nano-hard particles is 5:25:50-100:0.5:1-2.

Citation Information

Patent Citations

  • Fluorine-carbon powder paint and preparation method thereof

    CN109486298A

  • Graphene oxide modified curing agent, polyurethane coating and preparation method and application of graphene oxide modified curing agent

    CN109575225A